ANALISIS KESULITAN PENGUASAAN KOSAKATA DALAM PEMBELAJARAN MUATAN LOKAL BAHASA INGGRIS DI SEKOLAH DASAR - Nurlita, Preiti; Sunarsih, Diah; Tri Setiyoko, Didik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the types of difficulties experienced by fifth grade students in mastering English vocabulary in local content learning. This study uses a qualitative approach with a case study type. The data sources for this study were nine fifth grade students of SD Negeri 01 Larangan, class teachers, and teachers in charge of the local content subject of English. Data collection techniques were carried out through structured interviews, observation, and documentation. The results of the study showed that students experienced four main types of difficulties, namely: (1) difficulties in remembering and re-recognizing vocabulary that had been learned; (2) difficulties in translating vocabulary from English to Indonesian; (3) difficulties in spelling and writing vocabulary correctly; and (4) difficulties in pronunciation and lack of confidence in pronouncing English vocabulary. These difficulties are influenced by cognitive and psychological factors, as well as the minimal use of appropriate media and learning approaches. This study is expected to be used as evaluation material and consideration in designing English learning strategies that are more adaptive to students' needs.